Critical Hermeneutics Of The Representation Of Religious Minorities In Public Discourse In Indonesia - Muktasim Billah; Malikul Habsi (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study examines the representation of religious minorities in Indonesian public discourse using a critical hermeneutics approach integrated with critical discourse analysis. The scope of this study includes mass media discourse, public officials’ statements, policy documents, and popular religious discourses circulating in the public sphere. The objective of this study is to reveal patterns of representation of religious minorities, identify the ideologies and power relations underlying these representations, and explain their social implications for the position of religious minorities. This study employs a qualitative method with a critical-interpretative design, in which data are collected through documentary analysis and examined textually, contextually, and ideologically through hermeneutic reflection. The findings indicate that religious minorities are predominantly represented as social threats, deviations from majority norms, objects of state regulation, and passive subjects with limited discursive space. These representations function as symbolic mechanisms that reproduce majority dominance and structural injustice. The study concludes that critical hermeneutics is an effective approach for uncovering the relationship between meaning, ideology, and power in Indonesia’s religious public discourse.